Trends in stroke mortality in Latin America and the Caribbean from 1997 to 2020 and predictions to 2035: An analysis of gender, and geographical disparities - Torres Roman, J. Smith (2025)
Background Stroke is a leading cause of death and disability globally, with significant public health implications. In Latin America, while mortality rates have declined, the number of stroke cases has increased due to prevalent risk factors like high blood pressure and obesity. Unlike Europe, recent trends in stroke mortality in this region remain underreported. Objective This study evaluates stroke mortality rates in Latin America Latin American and Caribbean (LAC) countries from 1997 to 2020 and predictions to 2035. Methods This ecological observational study utilized mortality data from the World Health Organization database. Trends were analyzed using Joinpoint regression to evaluate the annual percent change (APC) by sex and country. Predicted mortality rates through 2035 were calculated using the Nordpred package in R. Changes in stroke mortality were assessed by disentangling the effects of population growth, aging, and risk factor modifications, based on age-specific rates and projections. Results were presented as absolute case numbers and relative percentages. Results From 1997 to 2020, twelve countries presented significant reductions in stroke mortality rates for men in LAC, the main ones being Chile (−4.2 %), El Salvador (−4.2 %), and Puerto Rico (−4.0 %). Thirteen countries reported a reduction in their mortality for women, mainly in Puerto Rico (−4.3 %), Chile (−3.7 %), Argentina, El Salvador, and Uruguay (−3.5 %). By 2035, an increase in deaths among men and women is expected, mainly due to the increase in population structure and size. However, a decrease in the mortality rate will be reported, mainly due to the reduction of risk factors. Conclusion Our final findings show a reduction in stroke mortality trends in LAC countries between 1997 and 2020, due to creating public awareness about vascular risk factors by authorities and the implementation of effective health policies. By 2035, an overall increase in mortality is expected, mainly due to population change in each country.